Biscoitos elaborados a partir de formulações alternativas - Almeida, Sabrina de Castro Penteado de (Universidade Federal de São Carlos, 2023)
Healthier products are becoming increasingly attractive to the consumer, requiring the study of alternative formulations in bakery products, in order to nutritionally enrich the product, without modifying its traditional characteristics. Due to the popularity and the consumption convenience of cookies, it becomes necessary to understand the impacts of these changes on sensory characteristics, as well as stability over time and the main microbiological threats present in these alternative formulations. Therefore, the goals of this work were to evaluate recent publications to understand the impact of the partial and total replacement of wheat flour by other functional ingredients, like fruits pulps such as caja and peach, as well as the addition of by-products, once considered residues, like fruit peels, fish carcasses, sugar cane bagasse, different flours (oats, corn, mycoprotein, broad bean, insect and young bamboo culm), coffee extract and sea grapes, cinnamon, insect oil and palm oil. From the review, it was noted the potential that several ingredients, common in the daily life, have to improve and add nutritional benefits to bakery products, without harming stability throughout shelf life or its sensory characteristics. In addition, it was analyzed different replacement levels of fat by hydrated chia seeds in cookies formulations. By the analysis of the cookies technological characteristics, such as texture analysis, water activity and moisture over time, it was possible to notice that this replacement by up to 40% did not impact negatively on the cookie characteristics.
Cookies made using alternative formulations
Keywords: Panificação; Formulações alternativas; Vida de prateleira; Biscoitos; Ingredientes funcionais; Sementes de chia hidratada; Bakery; Alternative formulations; Shelf life; Biscuits; Functional ingredient; Hydrated chia seeds; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS